The role of the nursing team in the context of the COVID-19: integrative review (Research, Society and Development, 2021)
The purpose of this study is to address the role of the nursing team in the context of the covid-19: and to identify in general. Method: This is a literature review through bibliographical research and for the construction of this study a search has been embodied in the databases of the Virtual Library on Health, such as Latin American Literature and the Caribbean in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO),employing the descriptors and their combinations in the Portuguese language appropriate to the DECS base (Descriptors in Health Sciences): COVID-19;Nursing professionals; Pandemic. Results: results show that the nurse is present throughout the care line to the patient with COVID-19, in the emergency and emergency services being responsible for the classification and measurement of risk in the ICU, taking care of the most critical conditions of the patient, which requires knowledge and science of the conduits and of course, at the level of primary attention, where by means of nursing consultation he can direct this patient to specific treatments or even follow the cases diagnosed as mild and simple of the disease. Conclusion: In the end, it is evident the importance and relevance of nursing staff care, because it is a multifaceted profession and because it has its performance guided by the Sistematization of Assistance. What guides his practices and all decision-making, the nurse acts in the most different scenarios and is even thought of as a strong point in combating epidemics and pandemics, all the way through, coexists with a scenario that causes him to face great pain, social and family isolation, as well as inappropriate working conditions, to be able to exercise care in a dignified and safe way, since it is inseparable from the front line against COVID-19.